3D planning in revision total knee arthroplasty following periprosthetic joint infection. A pilot study - Balato, Giovanni; Lenzi, Marco; de Matteo, Vincenzo; Verrazzo, Raffaele; de Giovanni, Roberto; Baldi, Dario; Mariconda, Massimo (Lo Scalpello - Journal, 2022)
Objective. Revision total knee arthroplasty (TKA) following a periprosthetic joint infection (PJI) represents a considerable challenge. The geometry of bony defects can be hard to assess on standard x-rays, thus requiring CT evaluation. CT data can be processed to create physical replicas by 3D printing. This model can be used as means of 3D planning through surgical simulation. This study aims to compare the ability to predict the need for augmentation to restore limb alignment between 2D and 3D planning. Methods. Ten consecutive patients undergoing second-stage TKA revision following PJI were included. Pre-operative CT and standard x-rays were obtained in all patients. CT data were used to produce a model using a 3D printer. The surgical simulation was then conducted using TKA revision instrumentation. Standard 2D planning and 3D planning were independently performed by two investigators. Interclass correlation coefficient was used to evaluate agreement on the use of augment. Results. For femoral augment, 3D and 2D accuracies were 80.8 and 37.5%, respectively. For tibial augment, 3D and 2D accuracies were 66.7 and 23.0%, respectively. Conclusions. 3D planning with surgical simulation has shown to be a valuable method to predict the need of augment in revision TKA following PJI.